Analisis Profil Layanan Terpadu Universitas Negeri Semarang berdasarkan Bahasa dan SOP yang Digunakan pada Masa Pandemi Covid-19 - Kurniawan, RM Praptono Putra Dwi; Kumorowati, Bhekti; Rahman, Fuad Ardani (Jurnal Penelitian Pendidikan, 2022)
Qualitative analysis is used to determine the ideal integrated service benchmarks during Covid-19 pandemic and how to improve the service. The final part is a SWOT analysis to find the right strategy to improve the integrated service by Customer Service (CS). The study was conducted on 375 respondents consisting of students and employees of Universitas Negeri Semarang who intensively communicated in two directions, namely via email and live chat. The results show that as many as 99% stated that they were satisfied with the integrated service before the face-to-face service was stopped during the covid-19 pandemic. After the COVID-19 pandemic, the satisfaction index decreased by 51% to 48% which was influenced by the emotions of customers from various ages so that the ideal service benchmarks during the pandemic is the use of a simple language easily understood by various generations and a concise and fast Standard Operating System (SOP). The SWOT strategy to improve services given by CS is to diversify the work system by utilizing strengths to overcome threats